HIV reprograms host m6Am RNA methylome by viral Vpr protein-mediated degradation of PCIF1 - Qiong Zhang; Yuqi Kang; Shaobo Wang; Gwendolyn Michelle Gonzalez; Wanyu Li; Hui Hui; Yinsheng Wang; Tariq M. Rana (Nature Communications, 2021)
m6Am is a modification of the 5′ end of mRNAs catalyzed by PCIF1. Here, Zhang et al. show that HIV infection induces a decrease in m6Am of cellular mRNAs through Vpr-mediated PCIF1 ubiquitination and degradation, resulting in increased HIV replication through regulation of host transcription factors.